Ecological risks in the economic transition conditions: Case study of reindustrialization of Valjevo - Đorđević Tijana (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu, 2017)
In this paper we presented the case study of reindustrialization of Valjevo - ecological risks in the conditions of economic transition. The crisis in Serbia during the 1990s had, among others, consequences visible in the manufacturing activities, especially industry. Nevertheless, Valjevo, as an evident example of favorable business environment, has made significant efforts to build an ambient for successful entrepreneurship. The aim of the paper is a critical presentation of the state of: economy and employment, processes of reindustrialization, environment and ecological risks in Valjevo. Special attention was given to the presentation of investment activities (direct investments recorded from companies from Austria, Italy, Slovenia, Croatia and other countries). The state of the environmental elements' quality has been estimated, and, on the basis of this, we can conclude that in Valjevo, it is mainly satisfactory, although, in some areas, more or less altered. Also, that a higher concentration of population and various economic activities, along with inherited industrial production (outdated technological processes, large quantities of industrial waste, low energy efficiency, lack of facilities and equipment for pollution reduction, etc.) are in conjunction with the possible occurrence of ecological risks. It was found that the current state of data and planning documents related to ecological risks assessment on the territory of Valjevo, is characterized by the basic availability of information on the dangers of possible natural disasters and technological accidents, as well as on severity of consequences that can cause (endangering the health, security and life of people, damage of a smaller or larger volume, changes of the environmental status, etc.). In order to reduce the consequences of possible ecological risks and develop a sustainable and effective way of their management, it is necessary to take measures of prevention and protection, both of the population, and of natural and material goods. Also, investors, as well as local government in Valjevo, have to follow legal norms and standards and work on: introducing and encouraging of new technologies use and developing of socially responsible business with expert services and professional personnel trained to control and manage possible ecological risks.